The Effect of Entrepreneurship Education on Entrepreneurial Intention With Human Capital As A Mediating Variable For Students in Tangerang - Rennee Maulana Arioseno; Hendy Tannady; Elissa Dwi Lestari (PT FORMOSA CENDEKIA GLOBAL, 2023)
There are still 8.4 million unemployed people in Indonesia as of February 2022. The high unemployment is coupled with the low interest in entrepreneurship that exists with only about 1.65% of Indonesian population. The purpose of this study is to determine how entrepreneurship education and human resources affect student interest in entrepreneurship in Tangerang. This research was conducted using quantitative methods with 103 samples taken using non-probability sampling with judgmental sampling. Data analysis in this study used SEM techniques with SmartPLS. According to this study, human resources do not significantly affect entrepreneurial interest, but they do significantly affect entrepreneurial education and entrepreneurial interest. This study also discovered that the association between entrepreneurship education and student interest in entrepreneurship is not mediated by human resources.